Strategi Pengembangan Pembelajaran Efektif Di Perguruan Tinggi - Haryono Haryono (LPPM Press, 2010)
Abstract: a lecturer quality is one of the keys to be succeed in teaching process. Thephenomenon says that a qualified lecturer will give good impacts to the graduation ofstudents. Effective teaching strategy is the important part in the teaching and learningprocess. To get a qualified teaching, a lecturer must use the effective teaching strategy.